Efektivitas Pembangunan Zona Integritas Menuju Wilayah Bebas Korupsi dan Wilayah Birokrasi Bersih Melayani di Kantor Pertanahan Kota Langsa - Thirarisani, Thirarisani; Daulay, Harmona; Madya, Faizal (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research aims to describe the effectiveness of the Integrity Zone (IZ) development towards Corruption-Free Zone and Clean Bureaucratic Service Area in Kantor Pertanahan Kota Langsa, as well as to identify the dimensions that influencing the effectiveness of IZ development towards Corruption-Free Zone and Clean Bureaucratic Service Area in the Kantor Pertanahan Kota Langsa. This study employs a qualitative approach with a descriptive method. Data collection is conducted through interviews, observations, and documentation. The research findings indicate that (1) In terms of program success criteria, the results show the effectiveness of IZ development towards Corruption-Free Zone and Clean Bureaucratic Service Area in the Kantor Pertanahan Kota Langsa. (2) The research findings related to target achievement criteria demonstrate that the Kantor Pertanahan Kota Langsa has effectively implemented the IZ development towards Corruption-Free Zone and Clean Bureaucratic Service Area. (3) Concerning program satisfaction criteria, this research shows that the IZ development towards Corruption-Free Zone and Clean Bureaucratic Service Area in the Kantor Pertanahan Kota Langsa has been carried out effectively. And (4) The research findings indicate the presence of internal and external factors influencing the IZ development towards Corruption-Free Zone and Clean Bureaucratic Service Area in the Kantor Pertanahan Kota Langsa.